Tax-benefit microsimulation model in Rwanda: A feasibility study - Naphtal Hakizimana; John Karangwa; Jesse Lastunen; Aimable Nsabimana; Innocente Murasi; Lucie Niyigena; Michael Noble; Gemma Clare Wright (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper assesses the feasibility of developing a tax and benefit microsimulation model in Rwanda. Tax-benefit microsimulation can be used to explore ways in which national development goals can be achieved in a cost-effective manner, and to assess the distributional effects of more comprehensive social security arrangements. The paper presents an account of Rwanda's tax and benefit policies as well as a possible underpinning dataset-the Integrated Household Living Conditions Survey-for a tax-benefit microsimulation model, concluding that developing such a model for Rwanda would be feasible.
Keywords: E62; H24; 330; tax; benefit; revenue; microsimulation